Battling bias: can two implicit bias remedies reduce juror racial bias? - Ruva, Christine L. (Psychology, crime & law, 2024)
Two studies examined the effectiveness of the Unconscious Bias Juror (UBJ) video and instructions at reducing racial bias in Black and White mock-jurors’ decisions, perceptions, and counterfactual endorsement in a murder (Study 1; N = 554) and battery (Study 2; N = 539) trial. Participants viewed the UBJ video or not, then read pretrial instructions (general or UBJ), a trial summary, and posttrial instructions (general or UBJ). In Study 1, juror race moderated the effect of defendant race on verdicts, culpability, and credibility. White, but not Black, jurors demonstrated greater leniency toward Black defendants for verdicts, culpability, and credibility. The UBJ video moderated the effect of defendant race on murder counterfactual endorsement. Only when the video was absent was jurors’ counterfactual endorsement higher for the White versus Black defendant, which mediated the effect of defendant race on White jurors’ verdicts. In Study 2, White jurors were more lenient regardless of defendant race. Instructions and juror race moderated the video’s effect on credibility ratings. The video only influenced Black jurors’ credibility ratings. In conclusion, the debiasing interventions were ineffective in reducing racial bias in jurors’ verdicts. However, they do impact aspects of juror attribution and may be effective with modification.